Linkage Analysis - Thomas, Duncan C. (Statistical Methods in Genetic Epidemiology, 2004)
Linkage analysis is the process of determining the approximate chromosomal location of a gene by looking for evidence of cosegregation with other genes whose locations are already known (i.e., marker genes). Cosegregation is a tendency for two or more genes to be inherited together, and hence for individuals with similar phenotypes to share alleles at the marker locus. Gene mapping is a huge topic, for which only a general introduction can be given here. Those interested in more detail can read one of the excellent textbooks by Ott (1999), Haines and Pericak-Vance (1998), or Pawlowitzki et al. (1997). Terwilliger and Ott (1994) provide a useful how-to manual of the mechanics of conducting a linkage analysis, based mainly on the LINKAGE package.